Performing Womanhood: Fictions of Love in Louisa May Alcott’s Behind a Mask - Stéphanie Durrans (European Journal of American Studies)
This article discusses Louisa May Alcott’s novella Behind a Mask in the light of Melville’s last novel, The Confidence-Man: His Masquerade (1857), arguing that, behind the mask of a sentimental novel that appears to conform to stereotypes, Alcott depicts a true-to-life heroine and shows how fiction can actually uncover the truth of life, how the many parts we play obfuscate our deeper nature and how a woman’s life in particular is nothing but a continuous performance on the social stage. In Behind a Mask, Alcott subtly reinstates “a woman’s power” (its subtitle) over and against a male-dominated novel and a male-dominated society.